2020
DOI: 10.5713/ajas.19.0987
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of injected fat-soluble vitamins in plasma and tissues of nursery pigs

Abstract: Objective: The objective of this experiment was to investigate the effects of fat-soluble vitamin injection on plasma and tissue vitamin status in nursery pigs.Methods: A total of 16 pigs (initial body weight: 7.15±1.1 kg) were allotted to 2 treatments at d 7 post-weaning. Pigs were fed a corn-soybean meal-based basal diet with no supplemental vitamin A and i.m. injected with 300,000 IU of retinyl palmitate, 900 IU of d-α-tocopherol and 30,000 IU of vitamin D<sub>3</sub> with control pigs having no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…The different responses of plasma vitamin A may have resulted from species differences, and the vitamin's form and dose may have potential effects on vitamin absorption. In addition, Jang et al reported that the plasma retinol value after feeding is associated with the relative growth rate and physiological status [19,20].…”
Section: Plasma Kinetic Behavior Of Different Forms Of Vitamin Amentioning
confidence: 99%
“…The different responses of plasma vitamin A may have resulted from species differences, and the vitamin's form and dose may have potential effects on vitamin absorption. In addition, Jang et al reported that the plasma retinol value after feeding is associated with the relative growth rate and physiological status [19,20].…”
Section: Plasma Kinetic Behavior Of Different Forms Of Vitamin Amentioning
confidence: 99%
“…This may be explained by saying that these sampling time points in the previous study were not ideal for plasma retinol kinetics. Raila et al studied pharmacokinetic behavior of vitamin A in dogs [21]; they observed that the peak plasma concentration was observed at 8 h after a single oral 3000 IU/kg vitamin A, and then plasma vitamin A was decreased until reaching 72 h. Jang et al elucidated that the retinol concentration in blood was associated with physiological status and performance of pig [22]. The present study was designed to determine the relative bioavailability of microencapsulated supplement compared to normal form of supplement.…”
Section: Discussionmentioning
confidence: 93%
“…Dependent upon the nutrient in question, a blood sample can sometimes determine nutrient deficiency or toxicity without having to euthanize animals for tissue sample collection. 2 Across many published references, serum or plasma samples have been analyzed to determine the vitamin A concentrations in pigs [3][4][5][6] without a consistent sampling protocol. However, serum and plasma are uniquely different biologically.…”
Section: Résumé -Influence De La Manipulation Pré-analytique D'échant...mentioning
confidence: 99%